2006
DOI: 10.1021/jm0606185
|View full text |Cite
|
Sign up to set email alerts
|

Selective Angiotensin II AT2 Receptor Agonists:  Arylbenzylimidazole Structure−Activity Relationships

Abstract: Structural alterations in the 2- and 5-positions of the first drug-like selective angiotensin II AT2 receptor agonist (1) have been performed. The imidazole ring system was proven to be a strong determinant for the AT2 selectivity, and with few exceptions all variations gave good AT2 receptor affinities and with retained high AT2/AT1 selectivities. On the contrary to the findings with AT1 receptor agonists, the impact of structural modifications in the 5-position of the AT2 selective compounds were less pronou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 31 publications
1
47
0
Order By: Relevance
“…1−3 In 2004, the first selective and drug-like AT 2 receptor agonist C21/ M024 (1) was disclosed, 4 and thereafter, a series of structural analogues with agonistic properties have been reported. 5,6 The activation of the AT 2 receptor is known to render a large number of diverse biological responses. 7,8 For example, receptor activation stimulates neurite outgrowth in neuronal cells, which is one of the first steps in neuronal differentiation.…”
Section: Abstract: At 2 Receptor Nonpeptide Ligands Agonist Antagomentioning
confidence: 99%
See 2 more Smart Citations
“…1−3 In 2004, the first selective and drug-like AT 2 receptor agonist C21/ M024 (1) was disclosed, 4 and thereafter, a series of structural analogues with agonistic properties have been reported. 5,6 The activation of the AT 2 receptor is known to render a large number of diverse biological responses. 7,8 For example, receptor activation stimulates neurite outgrowth in neuronal cells, which is one of the first steps in neuronal differentiation.…”
Section: Abstract: At 2 Receptor Nonpeptide Ligands Agonist Antagomentioning
confidence: 99%
“…This is also verified by compound 3, which previously has been tested for AT 1 receptor affinity (K i > 10 000 nM). 5 All compounds were evaluated for functionality in a neurite outgrowth assay with NG108-15 cells. The NG108-15 cells express mainly the AT 2 receptor in their undifferentiated state, and a three-day treatment with Ang II or the selective peptidic AT 2 receptor agonist CGP-42112 (N α -nicotinoyl-Tyr-(N α -CbzArg)-Lys-His-Pro-Ile) 23,24 induce neurite outgrowth.…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 99%
See 1 more Smart Citation
“…The substitution of the thienyl-phenyl to the biphenyl scaffold (resembling L162.782, Fig. 12) produced the equipotent C showing that the two scaffolds are bioisosteric in these compounds 43 . Compound D, a derivative of L162.782, was synthesized by Liu et al, in an attempt to develop new AT 2 R agonists as novel antihypertensive candidates.…”
Section: Fig 11: the Compounds With Dual At 1 R Antagonism And Pparγmentioning
confidence: 99%
“…We have also shown that 0968 the unsubstituted imidazole could be combined with substituents other than iso-butyl in the 5-postion of the thiophene. 20 Furthermore, we have shown that compounds where the thiophene has been exchanged with a phenyl maintain affinity and selectivity towards the AT 2 receptor. 20 Although the imidazole provided an excellent moiety for high affinity and selectivity towards the AT 2 receptor, it is known from literature that benzylic imidazoles frequently possess CYP 450 inhibition.…”
Section: Introductionmentioning
confidence: 97%